National Jail Census, 1999 ([Verlag nicht ermittelbar], 2002)
The 1999 Census of Jails is the seventh in a series of data collection efforts aimed at studying the nation's locally administered jails. Previous censuses were conducted in 1970, 1972, 1978, 1983, 1988, and 1993. The 1999 census enumerated 3,365 locally administered confinement facilities that held inmates beyond arraignment and were staffed by municipal or county employees. Among these were 47 privately operated jails under contract for local governments and 42 regional jails that were operated for two or more jail authorities. In addition, the census identified 11 facilities maintained by the Federal Bureau of Prisons that functioned as jails. The nationwide total of the number of jails in operation on June 30, 1999, was 3,376. For purposes of this data collection, a local jail was defined as a locally operated adult detention facility that receives individuals pending arraignment and holds them awaiting trial, conviction, or sentencing, readmits probation, parole, and bail-bond violators and absconders, temporarily detains juveniles pending transfer to juvenile authorities, holds mentally ill persons pending their movement to appropriate health facilities, holds individuals for the military, for protective custody, for contempt, and for the courts as witnesses, releases convicted inmates to the community upon completion of sentence, transfers inmates to federal, state, or other authorities, houses inmates for federal, state, or other authorities because of crowding of their facilities, relinquishes custody of temporary detainees to juvenile and medical authorities, operates community-based programs with day-reporting, home detention, electronic monitoring, or other types of supervision, and holds inmates sentenced to short terms. Variables include information on jail population by legal status, age and sex of prisoners, maximum sentence, admissions and releases, available services and programs, structure and capacity, facility age and use of space, expenditure, employment, staff information, and health issues, which include statistics on drugs, AIDS, and tuberculosis.